Efektivitas Pendekatan Jelajah Alam Sekitar Dengan Model Group Investigation Pada Materi Atmosfer Kelas X IPS SMA N 1 Bawang Tahun Pelajaran 2016/2017 - Hanifah, Utik Milati; Tukidi, Tukidi; Sriyanto, Sriyanto (Edu Geography, 2018)
This study is aiming to identify the effectiveness of natural roaming approach by using group investigation model on atmospheric materials in class X SMA N 1 Bawang. The criteria of effectiveness in this research are: 1) the ability of teacher in managing learning; 2)the mastery of students learning outcomes classically; 3) an achievement of students activity ; 4) studentsâ positive responses to the learning system. Design of this research is a pre-experimental study which had been conducted in SMA N 1 Bawang with the subject of class X IPS 3 which consists of 32 students. The result of the study shows that the teacherâs ability in managing the learning reach out 76,14 % , and it includes into good category. The mastery of classically students learning outcomes reach out 56.25%, so this criterion has not been fulfilled. Studentsâ activity in learning reach out 71.88%, and it includes into high category. Whereas the studentsâ response in adhering the learning reach out 97.66%, it includes into good category. Therefore, it could be concluded that Natural Roaming approach has not been effective applied in geography subject learning in atmospheric material for class X SMA N 1 Bawang 2016/2017 year school. Penelitian ini bertujuan untuk mengetahui efektivitas pendekatan jelajah alam sekitar dengan model group investigation pada materi atmosfer kelas X SMA N 1 Bawang. Kriteria efektivitas dalam penelitian ini adalah : 1) kemampuan guru dalam mengelola pembelajaran, 2) ketuntasan hasil belajar siswa secara klasikal, 3) ketercapaian aktivitas siswa, dan 4) tanggapan positif siswa terhadap pembelajaran. Desain penelitian ini adalah penelitian pre-eksperimen yang dilakukan di SMA N 1 Bawang dengan subjek kelas X IPS 3 yang berjumlah 32 siswa. Hasil penelitian menunjukkan bahwa kemampuan guru mengelola pembelajaran mencapai 76,14% dan masuk dalam kategori baik. Ketuntasan hasil belajar siswa secara klasikal mencapai 56,25% sehingga pada kriteria ini belum terpenuhi. Aktivitas siswa dalam pembelajaran mencapai 71,88% dan masuk dalam kategori tinggi. Sedangkan respon/tanggapan siswa dalam mengikuti pembelajaran mencapai 97,66% masuk dalam kategori baik. Dapat disimpulkan bahwa pendekatan jelajah alam sekitar belum efektif dalam pembelajaran geografi materi atmosfer kelas X di SMA N 1 Bawang tahun pelajaran 2016/2017.